2013
DOI: 10.1152/ajpgi.00265.2013
|View full text |Cite
|
Sign up to set email alerts
|

Gut-derived short-chain fatty acids are vividly assimilated into host carbohydrates and lipids

Abstract: Acetate, propionate, and butyrate are the main short-chain fatty acids (SCFAs) that arise from the fermentation of fibers by the colonic microbiota. While many studies focus on the regulatory role of SCFAs, their quantitative role as a catabolic or anabolic substrate for the host has received relatively little attention. To investigate this aspect, we infused conscious mice with physiological quantities of stable isotopes [1-(13)C]acetate, [2-(13)C]propionate, or [2,4-(13)C2]butyrate directly in the cecum, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
364
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 458 publications
(388 citation statements)
references
References 53 publications
14
364
3
7
Order By: Relevance
“…In a previous study performed in mice, cecal infusion of butyrate increased hepatic cholesterol synthesis, suggesting that butyrate might elevate plasma cholesterol 49. However, in another study performed in rats, hepatic cholesterol synthesis was reduced after ingestion of butyrate, albeit butyrate was given in combination with other SCFAs 50.…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study performed in mice, cecal infusion of butyrate increased hepatic cholesterol synthesis, suggesting that butyrate might elevate plasma cholesterol 49. However, in another study performed in rats, hepatic cholesterol synthesis was reduced after ingestion of butyrate, albeit butyrate was given in combination with other SCFAs 50.…”
Section: Discussionmentioning
confidence: 86%
“…Once SCFAs are transported to the liver, acetate and to a lesser extend butyrate are used as substrates in cholesterol synthesis and lipogenesis [33]. As mentioned earlier, through the activation of AMPK, SCFAs also regulate lipid-and cholesterol synthesis [42][43][44][45][46].…”
Section: Lipid Metabolismmentioning
confidence: 94%
“…For instance, it was shown that co-colonization of germ-free mice with the methanogenic archaeon Methanobrevibacter smithii as well as the saccharolytic bacterium Bacteroides thetaiotaomicron resulted in a significant increase in host adiposity, compared to mono-colonization with either one [32]. Moreover, after SCFAs have been formed, they are subjected to a high intracolonic interconversion due to microbial crossfeeding [33]. This shows that interventional studies with only one type of SCFA should be interpreted with caution as the observed effects might be due to other SCFAs after conversion in the gut.…”
Section: Production Of Scfasmentioning
confidence: 99%
See 1 more Smart Citation
“…The main products of intestinal fermentation of dietary fibers are short-chain fatty acids (SCFAs), of which acetate, propionate, and butyrate are the most abundant (6). Although these three SCFAs are rapidly assimilated into host carbohydrates and lipids-providing ;10% of our daily energy requirements (7)-there are clear differences in the way each is metabolized: propionate is primarily a precursor for gluconeogenesis, whereas acetate and butyrate are rather incorporated into fatty acids and cholesterol (8). Besides serving as an energy source, SCFAs also regulate metabolism by inhibition of histone deacetylases and chain-length-dependent activation of the endogenous G-protein-coupled receptor (GPR) 41 and 43 (9)(10)(11).…”
mentioning
confidence: 99%